Pelatihan Animasi Sederhana Bagi Guru Madrasah Ibtidaiyah Se-Kabupaten Magelang Guna Peningkatan Kualitas Pembelajaran di Masa Pandemi - Mashud Syahroni; Firstya Evi Dianastiti (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2021)
This community service activity seeks to solve problems that occur with partners about learning process during the COVID-19 pandemic in Indonesia. The online learning process has many problems and weaknesses when it is implemented in the past year. Likewise, the policy of the limited face-to-face learning making teachers have to extra efforts in conveying material to students. The short duration is used by the teacher to review online assignments so that the material is not in-depth. Therefore, the focus of the community service activity provided to partner teachers and principals of Madrasah Ibtidaiyah throughout Magelang Regency is making simple animated learning media using PowerPoint. The approach used in the training is the classical approach. Methods of implementing community service activities with training and practice. The training activities include the provision of introductory materials, demonstrations, and practical assignments. The results of the training evaluation show an increase in the ability of teachers in making learning media that is useful for improving the quality of learning during distance learning during the pandemic.